Perception of Vocational High School on the Existence of Probolinggo Municipality Mangrove Forest - Arief Yudi Andhika; Abdul Hakim; Harsuko Riniwati (Graduate Program, 2019)
This study aims to analyze and describe the perceptions of educational institution (SMKN 4 in Probolinggo Municipality) on the existence of the Probolinggo Municipality mangrove forest, and develop an alternative strategy for increasing perceptions of SMKN 4 in the management of Probolinggo Municipality mangrove forest. Data analysis was done using descriptive statistics and SWOT analysis. The results showed that the perceptions of students in SMKN 4 were in sufficient adequate, while the perceptions of employees in SMKN 4 were in adequate condition. The calculation results of the SWOT analysis, score for Strength is 1.78, Weakness 1.82, Opportunity 2.12, and Threats 1.77. Based on the scores of SWOT, so the SWOT coordinate can be calculated, -0.04 for the abscissa, and 0.35 for the ordinate. SWOT Coordinate (-0.04; 0.35) is positioned in quadrant IV, it means that SMKN 4 is expected to make efforts to support a change-oriented strategy. It can be done by minimizing the weaknesses and immediately achieve all available opportunities, with the implementation in the form of incorporating mangrove forest material in learning activities and carrying out mangrove forest management practices both independently and through collaboration with relevant parties such as fisheries services and environmental services.